Flight to liquidity and the Great Recession - Sören Radde (European Central Bank (ECB), 2014)
This paper argues that counter-cyclical liquidity hoarding by financial intermediaries may strongly amplify business cycles. It develops a dynamic stochastic general equilibrium model in which banks operate subject to agency problems and funding liquidity risk in their inter- mediation activity. Importantly, the amount of liquidity reserves held in the financial sector is determined endogenously: Balance sheet constraints force banks to trade off insurance against funding outflows with loan scale. A financial crisis, simulated as an abrupt decline in the collateral value of bank assets, triggers a flight to liquidity, which strongly amplifies the initial shock and induces credit crunch dynamics sharing key features with the Great Recession. The paper thus develops a new balance sheet channel of shock transmission that works through the composition of banks' asset portfolios.
Keywords: E22; E32; E44; 330; bank capital channel; credit crunch; funding liquidity risk; liquidity hoarding; macro-finance